Legal Status of Immovable Objects That Are Not Part of Joint Property in Mixed Marriage After Constitutional Court Decision No. 69/PUU-XIII/2015 - Nadiya Asvina; Adlin Budhiwan (Journal Equity of Law and Governance, 2025)
- This study analyzes the legal status and implications of immovable property not considered joint property in mixed marriages, based on Constitutional Court Decision No. 69/PUU-XIII/2015. It focuses on the legal consequences for foreign and Indonesian spouses. Mixed marriages involving foreign nationals (WNA) and Indonesians (WNI) face restrictions under agrarian law, limiting foreign ownership of immovable property. While marriage agreements can designate immovable property as personal assets of Indonesians, they risk violating agrarian laws if foreigners gain ownership. To prevent legal disputes with the National Land Agency (BPN), it is crucial to ensure compliance with agricultural regulations through supervision and adherence to legal provisions. This normative juridical study relies on literature-based research. Findings indicate that changes in policies may affect the legal status of immovable property in marriage agreements. Harmonizing conflicting laws and aligning them with Constitutional Court decisions are necessary to ensure the validity and legality of such agreements.